2021
DOI: 10.1002/nur.22170
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life among childhood cancer survivors in Korea: A quantile regression approach

Abstract: Cancer treatment in childhood may negatively affect survivors' quality of life. In this study, we aimed to determine the contributing factors for health‐related quality of life (HRQOL) in survivors of childhood cancer in Korea using quantile regression analysis. This study was a secondary analysis. Data were collected from 130 childhood cancer survivors (CCS) from November 2018 to July 2019. Participants completed the Memorial Symptom Assessment Scale, Depression Anxiety Stress Scale, Health‐Promoting Lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
(131 reference statements)
0
4
0
1
Order By: Relevance
“…Survivors of traumatic events such as being diagnosed with cancer and going through painful treatment processes try to understand the stressor, and spirituality plays an important role in coping with such events [61,62]. In our previous research, we have also found a positive relationship between spiritual growth and quality of life among CCS [63]. Our participants reported that they were positively influenced by mentors and parents who had children with childhood cancer during their survivorship periods, which indicates the importance of providing support after cancer treatment completion.…”
Section: Discussionmentioning
confidence: 81%
“…Survivors of traumatic events such as being diagnosed with cancer and going through painful treatment processes try to understand the stressor, and spirituality plays an important role in coping with such events [61,62]. In our previous research, we have also found a positive relationship between spiritual growth and quality of life among CCS [63]. Our participants reported that they were positively influenced by mentors and parents who had children with childhood cancer during their survivorship periods, which indicates the importance of providing support after cancer treatment completion.…”
Section: Discussionmentioning
confidence: 81%
“…Although more than 80% of individuals survive after childhood and adolescent cancer, as many as 60%-90% of long-term survivors experience unfavourable late effects or symptoms that can last months to years due to aggressive cancer treatments such as chemotherapy, radiation and surgery (National Cancer Institute, 2021c). Drowsiness, worrying, feeling nervous and dry mouth, which were prevalent in our review, were shown to affect the quality of life, increasing the risk of substance use and inadequate physical activity in CCSs who were relatively young and socially active (Hong et al, 2021;McDonnell et al, 2021;Noronha & Macdonald, 2016). However, the number of studies included for pooled prevalence ranged from 2-5, thus indicating a need for further studies to assess these symptoms and their relationships with health outcomes in the future.…”
Section: Discussionmentioning
confidence: 87%
“…Most cancer survivors have follow‐up schedules lasting up to 5 years post‐treatment, and symptom assessment and management are often not included in survivorship care plans. Hong et al (2021) reported that CCS were perplexed and frustrated when they experienced symptoms, not knowing where to seek help for symptom management during their survivorship period. CCS and AYA cancer survivors should therefore be educated about possible symptoms due to cancer treatment right from the time they receive the treatment, which should be monitored throughout their survivorship.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Por ser um componente cultural presente na maioria dos contextos sociais, a religiosidade/espiritualidade é um recurso subjetivo significativo presente nas vivências de familiares cuidadores de crianças e adolescentes com câncer, podendo interferir positiva ou negativamente na forma como lidam com a doença de seus filhos . Essa dimensão tem sido descrita na literatura científica como um elemento presente nos contextos de cuidado em saúde, sendo significativa para as pessoas, principalmente para aquelas que valorizam subjetivamente esses aspectos e os utilizam na adoção de determinados comportamentos e hábitos de vida (Hong et al, 2022;Zadeh et al, 2021).…”
Section: Discussionunclassified